2014
DOI: 10.1007/s10973-014-4166-8
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of amino acid containing chiral dicarboxylic acid between Mg–Al layered double hydroxide

Abstract: Layered double hydroxide (LDH) is a class of ionic lamellar solids with positively charged layers with two types of metallic cations and exchangeable hydrated gallery anions. The intercalation of organic anions, namely N,N 0 -(pyromellitoyl)-bis-L-a-amino acids diacid, into MgAl LDHs was studied for the first time. Chiral diacid monomers were synthesized in high yield from the reaction between pyromellitic dianhydride and different natural amino acids (L-isoleucine, S-valine, L-leucine, and L-phenylalanine) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The band around 447 cm −1 results from the lattice vibration of the hydroxide sheet and the broad band in the range of 3,200–3,700 cm −1 mainly from O–H groups of the hydroxide layers are observed. A broad band or shoulder is observed in all modified samples in the range 1,600–1,640 cm −1 , which may indicate the presence of H 2 O molecules as bending vibration appears in this region . The absorption bands at 2,930–3,100 cm −1 correspond to the ν asym and ν sym (C‐H) modes of CH 2 group in the chiral dicarboxylate molecules.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The band around 447 cm −1 results from the lattice vibration of the hydroxide sheet and the broad band in the range of 3,200–3,700 cm −1 mainly from O–H groups of the hydroxide layers are observed. A broad band or shoulder is observed in all modified samples in the range 1,600–1,640 cm −1 , which may indicate the presence of H 2 O molecules as bending vibration appears in this region . The absorption bands at 2,930–3,100 cm −1 correspond to the ν asym and ν sym (C‐H) modes of CH 2 group in the chiral dicarboxylate molecules.…”
Section: Resultsmentioning
confidence: 84%
“…Figure shows the FTIR spectra of MgAl‐LDH‐ CO32, modified LDH and l‐ isoleucine containing diacid. For neat LDH, the broad band in the range 3,200–3,700 cm −1 is because of the O–H stretching vibration of the metal hydroxide layer and interlayer water molecules . The band characteristic to metal‐oxygen bond stretching appears below 700 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…The XRD patterns of DLDH, PAI, PAIDN 2 and PAIAN 2 are shown in Figure . The presence of the main reflections in the lower angles in the XRD pattern of DLDH compared to the neat Mg‐Al LDH indicated that dicarboxylic anion 3 as the organic modifier are existed in the LDH interlayers. The XRD pattern of DLDH exhibited some main reflections at 4.62°, 8.55°, 10.24° and 21.99° ° of 2Ө.…”
Section: Characterization Of the Pai/ldh Nanocompositesmentioning
confidence: 99%
“…200°C corresponds to removal of weakly adsorbed water and water intercalated in the interlayer galleries of ZnAl-LDH. [43,44] The second weight loss (230-680°C) involves dehydroxylation of the brucite-like layers and loss of volatile species arising from decomposition of the interlayer carbonate anions. For diacid modified NiAl-LDH, the larger weight loss step within 400-600°C confirmed the presence of organic diacid in the interlayer of the LDH (Figure 7).…”
Section: Thermal Analysismentioning
confidence: 99%